Effect of the refrigeration system on in vitro quality and in vivo fertility of goat buck sperm - Mocé, Eva; Lozano-Palazón, Salvador A.; Martínez-Granell, María M.; Mocé, Maria Lorena; Gómez, Ernesto A. (MDPI, 2022)
Cooling goat sperm insemination doses to 4 °C causes a delay in their delivery. However, chilling these doses during the transportation period could expedite their delivery and the insemination process. In this study, an economical and simple apparatus for chilling goat semen doses in itinere was developed, and the in vitro quality and in vivo fertility of these doses were compared with those chilled by means of a programmable water bath in the laboratory at a rate of −0.18 °C/min. Of the tested prototypes, the one that provided an optimal combination of the chilling rate (average of −0.09 °C/min) and time required to reach 4 °C (3 h 45 min) was selected for further testing. Immediately after chilling and 24 h later, the doses chilled in the prototype were determined to be of higher quality than the samples chilled in the programmable water bath. Finally, the kidding rate was similar between the doses chilled in the programmable water bath (61.7% ± 7.1%) and in the prototype (56.1% ± 5.9%). In conclusion, successful chilling of goat sperm doses during transport is possible, thereby accelerating the delivery of insemination doses.